Workshop Bahaya Penggunaan Gadget pada Anak Usia Dini di Desa Keradenan Banyuwangi - Robisha Zarifa Ribaah; Fitriatul Masruroh (Lembaga Pengembangan Kinerja Dosen, 2025)
A workshop addressing the hazards of gadget usage in early infancy was conducted as community service at Posyandu ILP Kelinci, Keradenan Village, Banyuwangi Regency, East Java. This initiative aimed to enhance parents' awareness and understanding of the significance of gadget usage while equipping them with practical skills to assist their children in utilizing gadgets securely and constructively. The utilization of devices in early childhood can pose risks if not well monitored and restricted. This workshop activity must be undertaken to inform parents about the potential effects of devices on children. This program aims to educate parents and children about the advantages and dangers of gadget usage, along with strategies for prudent management. This workshop activity employs a hybrid approach, integrating lecture and question-and-answer techniques. Activity evaluation occurs both throughout the process and upon completion, concentrating on factors such as the attainment of objectives and the arrangement of activities. The method and results were evaluated through documentation. The assessment of the components of activity organization was conducted by observation. The success metrics for the execution of the workshop on the Dangers of Using Gadgets in Early Childhood employ two methodologies: (1) evaluation during the activity process, and (2) post-evaluation of workshop activities.